The pRB/E2F pathway - Lees, Jacqueline (Henry Stewart Talks, 2009)
The E2F transcription factors control cell cycle entry, The pRB/E2F pathway, pRB and E2F are both families of proteins, Differential roles of the pocket proteins, Repression and activation of E2F target genes is regulated by distinct E2F complexes, Rb mutant mice, Inhibition of the activating E2Fs is key to pRB's tumor suppressive activity, The activating E2Fs can also induce apoptosis and senescence genes in tumor cells, Role of pRB-E2F in DNA damage response, pRB contributes to the activation of pro-apoptotic genes in response to DNA damage